AIAA Guidance, Navigation, and Control Conference and Exhibit 2006
DOI: 10.2514/6.2006-6773
|View full text |Cite
|
Sign up to set email alerts
|

Central East Pacific Flight Routing

Abstract: This paper examines the potential benefits of transitioning from the fixed Central East Pacific routes to user-preferred routes. A minimum-travel-time, wind-optimal dynamic programming algorithm was developed and utilized as a surrogate for the actual userprovided routing requests. After first describing the characteristics of the flights utilizing the Central East Pacific routes for a five-day period, the results of both nominal and windoptimal routing simulations are presented. The average potential time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
(1 reference statement)
1
34
0
Order By: Relevance
“…Quasi-linearization has been shown to be effective in free flight problems with dense traffic conditions [30]. For creating wind-optimal free flight routes dynamic programming methods have shown to be effective [19]. Also rule based systems have been used to handle conflicts in free flight systems [17].…”
Section: Traditional Air Traffic Management Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quasi-linearization has been shown to be effective in free flight problems with dense traffic conditions [30]. For creating wind-optimal free flight routes dynamic programming methods have shown to be effective [19]. Also rule based systems have been used to handle conflicts in free flight systems [17].…”
Section: Traditional Air Traffic Management Approachesmentioning
confidence: 99%
“…In addition to being applied to the current airspace model, traditional optimization methods have also been applied to "free flight" paradigms, where aircraft can improve efficiency by using custom routes [8,17,19,25,30,35,50]. Quasi-linearization has been shown to be effective in free flight problems with dense traffic conditions [30].…”
Section: Traditional Air Traffic Management Approachesmentioning
confidence: 99%
“…A recent study examines the travel time and fuel usage savings of transitioning from the fixed Central East Pacific routes to user-preferred routes through develop minimum time wind-optimal routes using dynamic programming algorithm [6]. Several new operational strategies in air traffic management have been proposed that can potentially mitigate the impact of persistent contrail on climate change.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 10 the benefits of wind-optimal routing in the Central East Pacific region were evaluated. The study found an average time and distance savings of 4.8 minutes and 4.0 nmi per flight, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] In Ref. 7, it was shown that significant cost savings could be achieved without adversely impacting the traffic management functions.…”
Section: Introductionmentioning
confidence: 99%